ChemInform Abstract: Decarbonylative Radical Coupling of α‐Aminoacyl Tellurides: Single‐Step Preparation of γ‐Amino and α, β‐Diamino Acids and Rapid Synthesis of Gabapentin and Manzacidin A. Issue 24 (June 2015) - Nagatomo, Masanori; Nishiyama, Hayato; Fujino, Haruka; Inoue, Masayuki
Abstract: α‐Aminoacyl tellurides (III) and (IX) generate α‐amino carbon radicals via decarbonylation.